The formation of a carbon nanotube–graphene oxide core–shell structure and its possible applications - Dong, Xiaochen (2012)
A stable aqueous dispersion of hydrophobic single-walled carbon nanotubes (SWCNTs) and amphiphilic graphene oxide (GO) nano-sheets was produced by sonication mixing without assistance of any surfactant. Raman spectroscopy, scanning electron microscopy, transmission electron microscopy, and electrical characterization suggest that SWCNTs are completely wrapped by GO nano-sheets. The spontaneous formation of such a core–shell structure is due to the strong pi–pi stacking interaction between the two materials. The electronic coupling between them is evidenced by time-resolved fluorescence measurement. The potential of such a nanocarbon hybrid in optical limiting and supercapacitor applications is discussed.